Application of the T2 Hotelling Multivariate Control Chart for Online Learning Evaluation of Compulsory Statistics Courses in the Mathematics Undergraduate Study Program at Andalas University - Dina Putri Lestari; IZZATI RAHMI HG; YUDIANTRI ASDI (Jurnal Matematika UNAND, 2023)
The world of education is one aspect of life that has been affected by Covid-19, so on March 17, 2020 the Ministry of Education and Culture issued a Circular regarding online learning. Andalas University Mathematics Undergraduate Study Program is one of the study programs at Andalas University that also implements an online learning process. In this study, an online learning evaluation will be carried out based on the Mathematics Statistics I and Mathematics Statistics II courses in the Andalas University Mathematics Undergraduate Program in the odd semester 2019/2020 and the even semester 2019/2020. The analysis used to measure the success of online learning is the analysis of quality control using the T2 Hotelling control chart. In addition, an analysis of the process ability of the two courses will also be carried out. The results obtained by using the T2 Hotelling control chart are that the online learning process in the two courses is under control, while by analyzing the process ability it can be said that the online learning process in the two courses is still not working well, which means it is not fully within the limits. specifications that have been determined in the academic regulations of Andalas University.